2009
DOI: 10.1017/s1366728909990459
|View full text |Cite
|
Sign up to set email alerts
|

Morphological facilitation for regular and irregular verb formations in native and non-native speakers: Little evidence for two distinct mechanisms

Abstract: The authors compared performance on two variants of the primed lexical decision task to investigate morphological processing in native and non-native speakers of English. They examined patterns of facilitation on present tense targets. Primes were regular (billed-BILL) past tense formations and two types of irregular past tense forms that varied on preservation of target length (fell-FALL; taught-TEACH). When a forward mask preceded the prime (Exp. 1), language and prime type interacted. Native speakers showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
122
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(160 citation statements)
references
References 68 publications
17
122
9
Order By: Relevance
“…However, we note that our fi ndings are also compatible with those of Feldman et al ( 2010 ), with both their L1 and L2 participants, in that there was a lack of convincing evidence of decomposition of regular morphological form at an abstract level. This was noted by Feldman and colleagues particularly for their lower profi ciency learners, which is of some relevance to the current study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, we note that our fi ndings are also compatible with those of Feldman et al ( 2010 ), with both their L1 and L2 participants, in that there was a lack of convincing evidence of decomposition of regular morphological form at an abstract level. This was noted by Feldman and colleagues particularly for their lower profi ciency learners, which is of some relevance to the current study.…”
Section: Discussionsupporting
confidence: 69%
“…A lack of difference between L1 and L2 morphological storage and access was also proposed by Feldman, Kosti ć , Basnight-Brown, Filipovi ć Durdevi ć , & Pastizzo (2010). For native and nonnative speakers, they found evidence for crossmodal facilitation between morphologically related regular and irregular pairs compared to either unrelated or orthographic controls.…”
Section: Priming As a Test Of Morphological Representation In The L1 mentioning
confidence: 60%
“…For L2 speakers, a number of masked priming studies that directly compared derivation and inflection Kirkici & Clahsen, 2013;Silva & Clahsen, 2008) found efficient priming effects for derivation, but reduced or no priming for regular inflection in the same speakers. In contrast, other L2 studies reported significant priming effects for inflected words (Feldman et al, 2010;Foote, 2017). Models of morphological processing should be able to capture both the consistency and variability of the decomposition mechanism for different linguistic morphological types and speaker groups.…”
Section: Mechanisms Of Morphological Decompositionmentioning
confidence: 90%
“…Furthermore, L2 processing of morphologically complex words has been found to be more susceptible to surface form prime–target overlap than L1 processing. Unlike L1 control groups, advanced bilinguals showed significant priming effects for orthographically related items in a number of masked priming experiments (Diependaele, Duñabeitia, Morris, & Keuleers, ; Feldman, Kostić, Basnight‐Brown, Đurđević, & Pastizzo, ; Heyer & Clahsen, ; J. Li, Taft, & Xu, ; M. Li, Jiang, & Gor, ).…”
Section: Background Literaturementioning
confidence: 99%
“…The masked priming experimental paradigm (Forster & Davis, 1984), often combined with a lexical decision task, has been widely used by researchers ascribing to most, if not all, of the above accounts (e.g., Feldman, Kostić, Basnight-Brown, Durđević, & Pastizzo, 2010;Rastle & Davis, 2008). In this technique, the target word is preceded by two items: the first is a forward mask, consisting of a string of symbols (e.g., '#') matching the prime in length, and displayed for approximately 500 milliseconds; immediately afterwards, the prime is presented for a very short lapse, which varies widely (typically 34-60 ms; Rastle & Davis, 2008) but rarely exceeds 80 ms (Neubauer & Clahsen, 2009), in order to prevent conscious processing.…”
Section: Introductionmentioning
confidence: 99%